FINANCIAL DISTRESS ANALYSIS USING THE ZMIJEWSKI METHOD - Edon Ramdani (Universitas Pakuan, 2020)
This study aimed to determine the level of financial distress of the company using the Zmijewski method and conducted on three companies listed on the Indonesia Stock Exchange, namely PT Bakrieland Development Tbk, PT Central Omega Resources Tbk and PT Buana Lintas Lautan Tbk who received warnings from the IDX due to the delay in submitting financial reports. The results: the three companies are in good condition, with no financial distress. PT Bakrieland Development Tbk and PT Buana Lintas Lautan Tbk showed an increase in performance during the year 2016-2018 but PT Central Omega Resources Tbk decreased during the year 2016-2018. Companies are required to maintain the ability to meet their obligations and reduce the level of obligation so that it can be maintained does not lead to financial distress. Delays in the delivery of financial statements must be reduced so as not to harm investors. Analysis of financial distress needs to be continued to determine the company's financial condition. Contrast to previous studies that analyzed financial distress by comparing testing models and testing on companies listed on the IDX, this study focused on testing companies that received IDX warnings due to late financial reporting.